The efficiency frontier of markowitz and black-litterman model: A case study on the shariah-compliant stock in Jakarta Islamic Index - Subekti, Retno (AIP Conference Proceedings, 2022)
An efficient frontier (EF) is one of the important to portfolio construction. The EF is used to describe the highest expected return for a given level of risk or the lowest risk at a given level of return. This study aims to form the EF based on two models in the portfolio, such as a Mean-Variance (MV) from Markowitz and Black Litterman. We apply it to shariah-compliant stocks from the Jakarta Islamic Index (JII). The result shows that the EF of Black Litterman is in a better position with the lowest risk compared to the MV model